Cumans in the Latin Empire of Constantinople - Uzelac A (Золотоордынское обозрение)
Research objectives: An analysis of the background, circumstances and factors that led to the conclusion of the alliance between the Cuman fugitives from the Pontic Steppes and the Latin Empire of Constantinople, as well as its dissolution. Attention is also cast on some chronological issues and the participation of the Cumans in Frankish military campaigns. Research materials: Contemporary sources in which this episode is detailed, among them the most important being the works of Byzantine historian George Akropolites, French chronicler Alberic (Aubry) de Trois-Fontaines and another French author, Jean de Joinville, biographer of the French King Louis IX (1226–1270). Results and novelty of the study: The alliance concluded in Constantinople in the fall of 1239 between the Cumans and the Franks was without precedent in the western world. Together with the Cumans, the Frankish knights participated in a ceremony, performed according to nomadic customs. The ‘blood brotherhood’ was concluded between the two parties, and the alliance was consequently strengthened through the marital ties. Unlike Hungary, where the attempts to integrate the Cumans ended in failure due to the strong cultural and social differences between the newcomers and the local population, as well as internal instability, the Frankish elite in Constantinople was unanimous in their decision to compromise with the nomads, and there was no opposition to such an alliance. However, despite the fact that the Cumans were accepted in an exceptionally friendly manner, were held in high regard by the Frankish leadership and were allowed to retain their customs, the alliance did not last for long and was destined to be a failure. This was due to the complex internal and external factors such as lack of resources for the sustenance of the immigrants, the Mongol threat that loomed over the Latin Empire, and the untimely death of the Cuman leader Iona in 1241, whose personal authority was a guarantee of the alliance.